Review of the interactions of an ecological keystone species, Aechmea distichantha Lem. (Bromeliaceae), with the associated fauna. Issue 5 (1st February 2021) - Freire, Rodrigo M.; Montero, Guillermo A.; Vesprini, José L.; Barberis, Ignacio M.
ABSTRACT: Bromeliads interact with thousands of plants, animals and microorganisms. Some species are considered keystone species for providing shelter and protection to many species from vertebrates to microbes. Aechmea distichantha is a tank bromeliad distributed in the mid-latitudes of South America, known to interact with a wide variety of animal species. Studies aiming to provide inventories of the whole fauna associated are needed. An exhaustive academic review of interactions of this plant species with fauna was carried out including scientific articles, books, book chapters, theses, and reports published in different languages, where interactions between A. distichantha and an animal species were reported. These interactions were classified depending on the use that animals made of the plant and on the part of the plant involved. Since 1960, 347 animal morphospecies, involved in 495 interactions with A. distichantha have been documented. The plant was principally used as habitat or shelter, secondly used for food supply (herbivores, detritivores and predators), and finally for nesting. Morphospecies were mainly associated with the foliage and the phytotelmata, but also with the inflorescence, the inter-ramet space and the stolon. Invertebrates: Arachnids, mainly took refuge or shelter in the plant, and also found their preys. Insects, the most important class, took refuge on or inhabited in the plant and to a lesser extent used the plant for food supply. Vertebrates: amphibians, tortoises and reptiles exclusively used the plant for shelter, while birds and mammals mainly established feeding links. This is the first proposal tending to collect the whole set of animals interacting with this species. Aechmea distichantha is a keystone species that establish diverse, numerous direct and empirically detected interactions with fauna, and plays an important role in providing ecosystem services to humans.